2021
DOI: 10.3390/cancers14010057
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit of Resection Surgery for Pancreatic Ductal Adenocarcinoma with Liver Metastases: A Propensity Score-Matched SEER Database Analysis

Abstract: Guidelines do not recommend resection surgery for oligometastatic pancreatic ductal adenocarcinoma (PDAC). However, reports in small samples of selected patients suggest that surgery extends survival. Thus, this study aims to gather evidence for the benefits of cancer-directed surgery (CDS) by analyzing a national cohort and identifying prognostic factors that aid the selection of candidates for CDS or recruitment into experimental trials. Data for patients with PDAC and hepatic metastasis were extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…Two recent studies using the Surveillance, Epidemiology, and End Results (SEER) data found that PDAC patients with synchronous liver metastases who underwent pancreatectomy had better prognosis than those who did not undergo surgery. 13,14 However, the resection of metastatic liver lesions was not evaluated in studies based on SEER data. In SNUH cohort from this study, when dividing the cytoreductive surgery plus chemotherapy group according to curative-intent, median (IQR) OS was best for patients who underwent curativeintent surgery (22.0 [13.0-92.0] months) compared to those underwent noncurative intent surgery (15.0 [10.0-28.0] months), or (8.0 [5.0-12.0] months) chemotherapy alone (P < .001; Figure S4a).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies using the Surveillance, Epidemiology, and End Results (SEER) data found that PDAC patients with synchronous liver metastases who underwent pancreatectomy had better prognosis than those who did not undergo surgery. 13,14 However, the resection of metastatic liver lesions was not evaluated in studies based on SEER data. In SNUH cohort from this study, when dividing the cytoreductive surgery plus chemotherapy group according to curative-intent, median (IQR) OS was best for patients who underwent curativeintent surgery (22.0 [13.0-92.0] months) compared to those underwent noncurative intent surgery (15.0 [10.0-28.0] months), or (8.0 [5.0-12.0] months) chemotherapy alone (P < .001; Figure S4a).…”
Section: Discussionmentioning
confidence: 99%
“…A study of 69 participants with concurrent liver metastases showed that participants who underwent simultaneous resection had a longer survival time significantly compared to those who did not undergo surgical resection (14 months vs 8 months, p < 0.01 ) ( 49 ). An analysis of the SEER database suggests that CDC (cancer–directed surgery) is capable of prolonging survival of oligometastatic PDAC patients ( 50 ). In addition, locally-ablative treatments like microwave ablation (MWA) and radiofrequency ablation (RFA) are considered complementary to radical surgery ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such treatment options should be considered for carefully selected patients. Cancer-directed surgery reliably increased the median OS from 5 to 10 mo in patients with pancreatic ductal adenocarcinoma with LM in a propensity-matched analysis of the SEER database[ 33 ]. Furthermore, several types of PNETs are treated with cancer-directed surgery, regardless of LM[ 34 ].…”
Section: Discussionmentioning
confidence: 99%